Development and Validation of a Reversed Phase High Performance Liquid Chromatography-Photodiode Array Detection Method for Simultaneous Identification and Quantification of Coumarin, Precocene-I, β-Caryophyllene Oxide, α-Humulene, and β-Caryophyllene in Ageratum Conyzoides Extracts and Essential Oils from Plants. (12th March 2020) - Shah, Sonal; Dhanani, Tushar; Sharma, Sonu; Singh, Raghuraj; Kumar, Satyanshu; Kumar, Bhanu; Srivastava, Sharad; Ghosh, Srikant; Kumar, Rajesh; Juliet, Sanis
Abstract: Background: Ageratum conyzoides is an aromatic plant. It is considered as an invasive and cosmopolite weed, widely spread in tropical and subtropical regions. Phytochemicals such as benzopyrenes, flavonoids, and terpenoids are reported from A. conyzoides. Objective: Development and validation of a reversed-phase HPLC-photodiode array (PDA) detection method for simultaneous identification and quantification of coumarin, precocene-I, β-caryophyllene oxide, α-humulene, and β-caryophyllene in extracts of A. conyzoides and essential oils was carried out. Methods: Separation of analytes was achieved on a RP-18 (250 mm × 4.6 mm, 5 µm) column using a solvent system comprising of a mixture of acetonitrile and water with 0.05% trifluoroacetic acid in gradient elution mode at ambient temperature with flow rate of 1 mL/min. Results: The retention time of coumarin, precocene-I, β-caryophyllene oxide, α-humulene, and β-caryophyllene was 4.38, 12.86, 20.10, 33.34, and 35.11 min, respectively. Limits of detection for coumarin, precocene-I, β-caryophyllene oxide, α-humulene, and β-caryophyllene were 2.5, 2.5, 2.5, 0.025, and 2.5 µg/mL, respectively. Similarly, LOQ were 10, 10, 10, 0.10, and 10 µg/mL for coumarin, precocene-I, β-caryophyllene oxide, α-humulene, and β- caryophyllene, respectively. Repeatabilities (RSD, %) values for intraday and interday precision for coumarin, precocene-I, β-caryophyllene oxide, α-humulene, and β-caryophyllene was 0.765–2.086 and 0.886–2.128; 0.879–1.672 and 0.979–1.825; 0.696–2.418 and 0.768–2.592; 1.728–2.362 and 1.965–2.378; 1.615–2.897 and 1.658–2.906, respectively. Conclusions: The separation of five analytes was achieved within 50 min. The developed and validated HPLC-PDA method was successfully applied for identification and quantification of above five analytes in A. conyzoides extracts and essential oils. The method could be used for meeting the characterization criteria of phytoformulations.